2007
DOI: 10.1093/hmg/ddm155
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cell proliferation and increased apoptosis are significant pathological mechanisms in a murine model of mild pseudoachondroplasia resulting from a mutation in the C-terminal domain of COMP

Abstract: Pseudoachondroplasia (PSACH) is one of the more common skeletal dysplasias and results from mutations in cartilage oligomeric matrix protein (COMP). Most COMP mutations identified to date cluster in the TSP3 repeat region of COMP and the mutant protein is retained in the rough endoplasmic reticulum (rER) of chondrocytes and may result in increased cell death. In contrast, the pathomolecular mechanism of PSACH resulting from C-terminal domain COMP mutations remain largely unknown. This study describes the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
169
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(193 citation statements)
references
References 46 publications
24
169
0
Order By: Relevance
“…This is further supported by the minimal chondrocyte pathology observed in two knockin COMP mutation mouse models that do not completely recapitulate PSACH chondrocyte pathology and clinical manifestations. [50][51][52][53] Altogether, this suggests that the total amount of COMP is an important factor in MT-COMP pathology and that reduction of total COMP with ASOs ameliorates the disease process.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is further supported by the minimal chondrocyte pathology observed in two knockin COMP mutation mouse models that do not completely recapitulate PSACH chondrocyte pathology and clinical manifestations. [50][51][52][53] Altogether, this suggests that the total amount of COMP is an important factor in MT-COMP pathology and that reduction of total COMP with ASOs ameliorates the disease process.…”
Section: Discussionmentioning
confidence: 97%
“…This is further supported by the minimal chondrocyte pathology observed in two knockin COMP mutation mouse models that do not completely recapitulate PSACH chondrocyte pathology and clinical manifestations. [50][51][52][53] Altogether, this suggests that the total amount of COMP is an important factor in MT-COMP pathology and that reduction of total COMP with ASOs ameliorates the disease process.We show that mitigation of the chondrocyte pathology was achieved by administering ASO1 for 3 weeks at 180 mg/kg/week. This level of COMP knockdown (38% hCOMP and 60% mCOMP) reduced intracellular retention of MT-COMP, chondrocyte death, and inflammatory markers and partially restored normal levels of chondrocyte proliferation ( Figures 5B-5J and 6).…”
mentioning
confidence: 97%
“…In addition, recent studies have shown that mutations that cause misfolding of matrix proteins can activate a cellular stress response: the unfolded protein response. This has been shown with COMP and matrilin 3 mutations in multiple epiphyseal dysplasia and type X collagen in Schmid metaphyseal chondrodysplasia (48)(49)(50). This unfolded protein response unleashes a cascade of downstream gene expression changes that can include changes in cellular differentiation, increased protein breakdown, and apoptosis.…”
Section: Chondrodysplasias and Molecular Mechanisms In Oamentioning
confidence: 91%
“…The chaperone activity of Pdia4 (ERp72) is of particular interest because ERp72 forms stable complexes with disease-causing COMP and matrilin-3 mutants. Accumulation of these complexes in dilated ER cisternae is a hallmark of multiple epiphyseal dysplasia and pseudoachondroplasia (60 -62), and the resulting ER stress affects normal chondrocyte differentiation and organization in the growth plate (63)(64)(65). ER stress induced by misfolding of collagen X in hypertrophic chondrocytes also contributes to the pathology of Schmid metaphyseal chondrodysplasia, type Schmid (66,67), but the role of specific ER chaperones is not known.…”
Section: Regulation Of Specific Endoplasmic Reticulum-resident Proteimentioning
confidence: 99%